METHODS AND QUALIFICATIONS FOR MAN MADE ENVIRONMENTAL EMERGENCIES IN THE REPUBLIC OF UZBEKISTAN - Gulzhamol Nuraddinovna Khidirbayeva (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses methods and qualifications in cases of environmental and emergency situations in the republic, a brief analysis of measures to eliminate and prevent the population and territories from emergency situations is made.